Особливості формування управління інноваційними процесами аграрного сектору національної економіки - Павлова, Галина Євгеніївна; Pavlova, G. (Дніпровський державний аграрно-економічний університет, ТОВ `ДКС Центр`, 2015)
В останні роки питання переходу вітчизняної економіки і, зокрема, аграрної її сфери на інноваційний шлях розвитку досить широко обговорюються вченими, відбиваючись у їх наукових дослідженнях, а також знаходяться в центрі уваги керівництва країни. Підвищення економічної ефективності сільськогосподарського виробництва на основі використання інноваційних розробок є основним стратегічним напрямом подолання системної кризи в аграрному секторі. У цьому полягає специфіка застосування основних понять теорії інноваційної економіки до аграрного сектору національної економіки, яка обумовлена специфічними особливостями самої галузі, розбудованої її технологічних процесів у процеси, що відбуваються в природному середовищі, участю у виробництві живих організмів, які можуть також бути об'єктами інновацій. Відмінною рисою інновації в аграрному секторі є саме обов'язкова наявність компонента, який, будучи частиною навколишнього середовища, без участі людини існувати не може. У відповідності з даним визначенням необхідно представити і класифікацію інновацій в аграрному секторі національної економіки. In recent years, the issue of transition of the domestic economy and, in particular, agricultural areas for its innovative way of development is widely discussed by scientists, reflected in their research and are the focus of leadership. Increasing economic efficiency of agricultural production through the use of innovation is the main strategic direction to overcome the crisis in the agricultural sector. A significant increase in production, shortening the payback of invested capital and increase the investment attractiveness of farms, as the study of foreign experience, achieved provided innovation. However, in most agricultural organizations of their own are unable to exercise reproductive processes through the introduction of new techniques and technologies in the current economic environment. Currently, a new paradigm of the world economy based on innovation. Innovations are a strategic driver of economic growth, affecting the structure of social production, stabilize the social situation. The world-wide, long-term sustainable economic development depends largely not on the resources available and on innovation activity. Through innovation science has become a direct productive force, and innovation in the form of intangible assets — primarily capital for economic development. The author states that the most correct classification criteria of innovation is the principle of separation of target orientation, directional innovation on a particular object or process. In any sector innovation are the objects of economic elements involved in production processes. As part of this approach, innovation in agro — innovation is affecting directly (or indirectly, within the process chain) processes, to which people, machinery and equipment, as well as elements of biological systems (animals, plants, etc.). The existence of which in the environment (without human intervention) impossible or possible only with the loss of basic functional characteristics. Thus innovation as an economic category may have different meanings in different contexts, the choice of which depends on the specific objectives change, the analysis of economic relations in the sphere of innovations. Encyclopedic definition of innovation allows us to understand its meaning only in comparison with the term "innovation". Innovation (Eng. Innovation — innovation, innovation) — is introduced (applied, used) innovation as a result of practical development of a new process, product or service. Innovation (lat. Novation — change, update) is a kind of innovation that was not before: a new phenomenon, discovery, invention, a new method to meet social needs and more. In this context, innovation should be understood as implemented innovations; regardless of scope, it realized innovation. Innovation — a successful application (implementation) of excellence. The author gives the author's definition of innovation development of the agricultural sector of the national economy — a successful development of social, economic, educational, administrative and other areas on the basis of various innovations, this chain constant innovations implemented in the agricultural sector of the national economy.
Features of formation of managing innovation processes of the agricultural sector of the national economy
Keywords: аграрний сектор; the agricultural sector; інновації; innovation; національна економіка; national economy; середовищні компоненти; environmental components; конкурентоспроможність; competitiveness; інновацій в агарному секторі; innovation specifics into consideration